Pengaruh Literasi Keuangan, Kontrol Diri dan Lingkungan Teman Sebaya Terhadap Perilaku Konsumtif (Studi Pada Pengguna Aplikasi Shopee Generasi Millennial di DKI Jakarta) - Nadiah Nurli Fadilah; Karuniana Dianta; Aditya Pratama (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The aim of this research is to analyze "The Influence of Financial Literacy, Self-Control and Peer Environment on Consumptive Behavior (Study of Millennial Generation Shopee Application Users in DKI Jakarta)". The method used in this research is a quantitative method. The data source used in this research is primary data. The data obtained was processed using classical assumption testing, multiple linear regression analysis and hypotheses with the analysis tool used is SPSS 27. The research results show that financial literacy does not have a significant influence on consumptive behavior, while self-control and peer environment have a significant positive influence on consumptive behavior. Meanwhile, the results of the simultaneous test state that financial literacy, self-control and peer environment have a significant positive effect on consumer behavior simultaneously. The findings of this research underline that the importance of financial literacy does not mean that millennials can apply it in their daily lives. Meanwhile, in controlling their own abilities, millennials are able to restrain themselves from becoming consumptive people, apart from that, the influence of their peer environment is also important so that millennials can avoid consumptive behavior.